Stadium dan Tingkat Parasitemia Plasmodium Falciparum pada Sediaan Darah Malaria - Nanda Yuan Savera (Jaringan Laboratorium Medis, 2019)
Malaria is an infectious disease caused by plasmodium parasites that are infected through the bite of anopheles female mosquito. Malaria has several stages such as tropozoites, schizonts and gametocytes stage. Plasmodium falciparum is the most dangerous species because of the potential to cause hyperparasitemia and complications. Banjarnegara is one of endemic areas. The cases of malaria in 2017 from January to October, the most common type of plasmodium found in community health care center Banjarmangu 1 district Banjarnegara is Plasmodium falciparum. Research method was observational study with descriptive research criteria. The result of this study from 24 blood samples examined were stadium with tropozoites stage amount 14 samples, stadium with tropozoit-schizonts stage of 3 samples and stadium with tropozoit-gametocytes stage of 7 samples. Levels of parasitemia was found 2 levels of parasitemia that is 0,02% and 0,2%. there were 3 stadium found that are tropozoit, tropozoit-schizonts and tropozoit-gametocytes. To level of parasitemia, there was no found  hyperparasitemia of all the examined samples.